PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS PADA SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN KARYAWAN (STUDI KASUS: PT WEST HOME PROPERTY) - Ahmad Satibi; Kussigit Santosa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The concept of a Decision Support System (DSS) was first expressed in 1971 by Michael Scott Morton with the term Management Decision System. Then a number of companies, research institutions and universities began to conduct research and build decision support systems, so it can be concluded that this decision support system is a computer-based system intended to help decision makers in utilizing certain data and models to solve various unstructured problems. Mistakes in choosing employees, of course, have a bad impact on the company itself, because it can directly affect the productivity and performance of the company. This is supported by reports of entry and exit of employees from this Company that there are still a significant number of employees leaving, where the reason for the employee leaving is dominant with employees who do not pass the probationary period and leave because they are unable to meet the demands of the work given, so this needs improvement so that the employees accepted are employees with the best results that can be said to be competent and in accordance with the criteria  Existing positions so that in the future it is expected to reduce the number of employees leaving. To overcome this problem, a decision support system was created using the Analytical Hierarchy Process (AHP) method. In this study using the Analytical Hierarchy Process (AHP) method where the flow and stages used include observation, interviews, analysis, implementation, and testing. The result of this study is a decision support system that is expected to facilitate the selection process for employee acceptance at PT West Home Property.